2008
DOI: 10.1111/j.1532-950x.2008.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Versus Arthroscopy for Detection of Canine Elbow Dysplasia Lesions

Abstract: CT can provide valuable information for the investigation of dogs with elbow dysplasia, but the absence of CT signs (or the absence of arthroscopic abnormalities) does not rule out elbow lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
198
2
30

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(238 citation statements)
references
References 25 publications
8
198
2
30
Order By: Relevance
“…In particular, diseases involving the shoulder joint and adjacent structures should be excluded as causes of thoracic limb lameness. 26 CT and more recently MRI scans are increasingly used to evaluate elbows where changes are equivocal on radiographic assessment 27 ; however, arthroscopic evaluation constitutes the most important single interrogation directing our decision-making process for MCD with or without pathology of the medial aspect of the humeral condyle. We have observed equivocal findings on both CT and MRI where subchondral pathology was subsequently proven by histologic examination of coronoid specimens after arthroscopically identified MCD.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, diseases involving the shoulder joint and adjacent structures should be excluded as causes of thoracic limb lameness. 26 CT and more recently MRI scans are increasingly used to evaluate elbows where changes are equivocal on radiographic assessment 27 ; however, arthroscopic evaluation constitutes the most important single interrogation directing our decision-making process for MCD with or without pathology of the medial aspect of the humeral condyle. We have observed equivocal findings on both CT and MRI where subchondral pathology was subsequently proven by histologic examination of coronoid specimens after arthroscopically identified MCD.…”
Section: Diagnosismentioning
confidence: 99%
“…This disparity effectively exposes the coronoid process of the ulna to increased load-bearing forces from the humerus throughout the full range of elbow movement. MCP disease has been identified by CT and arthroscopy in the absence of overt static incongruity, 27 so it seems unlikely that static incongruency plays a major role in some dogs, 11 although where definitively identified, MCD should be considered a likely sequel. This form of incongruency might be expected to result in pathologic change focused at the tip of the medial aspect of the coronoid process but further biomechanical modeling is needed to validate this hypothesis.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…Putatively, their role may be less clinically important than persistent cartilage and subchondral bone erosion that has been documented in the absence of free fragmentation. 17 Conventional focal treatment of coronoid pathology depends on healing occurring in the persistent friction environment of the medial compartment of the elbow. More aggressive arthroplasty to lower the joint surface of the MCP by motorized shaving during arthroscopic procedures has been advocated to ameliorate the effects of ''medial compartment'' pain associated with joint surface friction.…”
mentioning
confidence: 99%
“…6,18 Surgical debridement of malaciac cartilage has been advocated to allow assessment of subchondral bone. 17 It has been suggested that ''soft'' and ''yellow'' subchondral bone be debrided until hemorrhage of the underlying bone occurs and it resembles a more normal ''hard'' and ''white'' morphology. 19 Hemorrhage may vary with raised intra-articular pressures resulting from fluid infusion during arthroscopic examination.…”
mentioning
confidence: 99%
“…Lesions of the medial coronoid process were the most frequent diagnosis. Since computed tomography has a sensitivity and specificity of 88% and 85% respectively for the detection of fragments of the medial coronoid process, the distribution of lesions can be considered quite accurate, even in the absence of an arthroscopic confirmation (23,24).…”
Section: Discussionmentioning
confidence: 99%